Riluzole 5 mg/mL oral suspension: for optimized drug delivery in amyotrophic lateral sclerosis - Dyer AM; Smith A (Dove Medical Press, 2016)
Ann Margaret Dyer, Alan Smith PharmaSci Consulting Limited, Nottingham, UK Abstract: The aim of the present work is to extensively evaluate the pharmaceutical attributes of currently available riluzole presentations. The article describes the limitations and risks associated with the administration of crushed tablets, including the potential for inaccurate dosing and reduced rate of absorption when riluzole is administered with high-fat foods, and the advantages that a recently approved innovative oral liquid form of riluzole confers on amyotrophic lateral sclerosis (ALS) patients. The article further evaluates the patented and innovative controlled flocculation technology used in the pseudoplastic suspension formulation to reduce the oral anesthesia seen with crushed tablets, resulting in optimized drug delivery for riluzole. Riluzole is the only drug licensed for treating ALS, which is the most common form of motor neurone disease and a highly devastating neurodegenerative condition. The licensed indication is to extend life or the time to mechanical ventilation. Until recently, riluzole was only available as an oral tablet dosage form in the UK; however, an innovative oral liquid form, Teglutik® 5 mg/mL oral suspension, is now available. An oral liquid formulation provides an important therapeutic option for patients with ALS, >80% of who may become unable to swallow solid oral dosage forms due to disease-related dysphagia. Prior to the launch of riluzole oral suspension, the only way for many patients to continue to take riluzole as their disease progressed was through crushed tablets. A novel suspension formulation enables more accurate dosing and consistent ongoing administration of riluzole. There are clear and important advantages such as enhanced patient compliance compared with crushed tablets administered with food or via an enteral feeding tube and the potential for an improved therapeutic outcome and enhanced quality of life for ALS patients. Keywords: amyotrophic lateral sclerosis, riluzole, dysphagia, patient compliance, oral liquid